Reply - Linebaugh, Peter (Labour / Le Travail, 1984)
Replies to Robert Sweeny's critique in the same issue by restating the core argument from the article, "All the Atlantic Mountains Shook," published previously in the journal (no. 10, November 1982) with additional documentation.